Core contents for a menopausal health literacy intervention for South Korean middle-aged women: an e-Delphi study - Haein Lee; Junghee Kim (BMC, 2024)
Abstract Background The attention on improving health literacy (HL) for self-management at the population level in many countries has been increasing. Although self-management among middle-aged women in the menopausal transition are important public health issues, few studies have developed the menopausal HL intervention reflecting the multidimensional aspects of HL. We aimed to generate consensus from an expert panel on the core contents of the menopausal HL intervention for middle-aged women based on the HL conceptual framework of the European Health Literacy Survey. Methods The panel comprised 20 experts from multiple disciplines (nursing, medicine, public health, and food and nutrition). We conducted the e-Delphi process in three rounds, asking the panel to evaluate and prioritize the appropriateness of the core contents and provide open-ended responses to additional comments about the menopausal HL intervention. The e-Delphi questionnaire was developed based on the HL framework, integrating health and HL domains. Results The experts reached a consensus on 38 components of the intervention. Among the 19 components of the four health domains, health topics in healthcare and disease prevention were more appropriate than those in health promotion. For the 19 HL competency components, strengthening the ability to access, appraise, and apply health information was more important than strengthening the ability to understand information. Finally, a consensus was achieved on the 12 priorities for intervention content by HL domains integrated with health domains. For example, contents included proper access to reliable information resources, understanding the definition and process of menopause, judging abnormal health symptoms, and performing the health checkups necessary for menopausal women. Conclusions Our findings provide evidence for HL skills that nurses and other health professionals can consider when developing interventions to improve self-management among middle-aged women. Future research should focus on incorporating the core contents of multidimensional HL skills into menopausal HL interventions to improve self-management among middle-aged women.